PENGEMBANGAN SEKTOR-SEKTOR EKONOMI DI TIAP KECAMATAN DI KABUPATEN MAGELANG - Rifki Adhitama (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
The purpose of the study was to identify and determine the sectoral planning of the leading sectors to be developed to support the economic growth of each district in the district Magelang and develop strategies in each district development planning in Magelang districts to spur economic growth. The method used in this study, namely Location Quotient, Shift Share and Klassen Typology sectoral approach. The result showed that the service sector, agriculture and trade in the district Magelang dominate key sectors that exist in each district in the district Magelang. The subdistrict that be recommended as development in service sector area they are Windusari subdistrict, Dukun subdistrict, Ngluwur subdistrict, Salaman subdistrict, Muntilan subdistrict, Secang subdistrict, Tegalrejo subdistrict, Ngablak subdistrict and pakis subdistrict. Subdistrict that be recommended as development sector areas in agliculture they are kajoran subdistrict, Bandongan subdistric, Borobudur subdistric, Tegalrejo subdistric, Sawangan subdistric, Pakis subdistric, Srumbung subdistric, and Ngablak subdistric. . The subdistrict that can be recommended as development commerce, hotel and restaurant sector area they are Borobudur subdistrict, Mungkid subdistrict, Candimulyo subdistrict, mertoyudan subdistrict, Sawangan subdistrict and Secang subdistrict.